Modelling and design methodology for fully-active fixtures - Papastathis, Thomas (2011)
Fixtures are devices designed to repeatedly and accurately locate the processed workpiece in a desired position and orientation, and securely hold it in the location throughout the manufacturing process. Fixtures are also charged with the task of supporting the workpiece to minimise deflection under the loads arising from the manufacturing process. As a result, fixtures have a large impact on the outcome of a manufacturing process, especially when the workpiece presents low rigidity. Traditionally, in manufacturing environments, where thin-walled components are produced, the utilised fixtures are dedicated solutions, designed for a specific workpiece geometry. However, in the recent decades, when the manufacturing philosophy has shifted towards mass customisation, there is a constant technological pull towards manufacturing equipment that exhibits high production rates and increased flexibility/reconfigurability, without any compromise in the quality of the end result. Therefore, fixtures have been the focal point of a plethora of research work, targeting mainly towards either more reconfigurable, or more intelligent/adaptive solutions. However, there have been no attempts so far to merge these two concepts to generate a new fixturing approach. Such an approach, referred to in this work as fully-active fixrturing, would have the added ability to reposition its elements and adapt the forces it exerts on-line, maximising the local support to the workpiece, and thus reducing vibration amplitude and elastic deformation. This results in a tighter adherence to the nominal dimensions of the machined profile and an improved surface-finish quality.